Pertanggungjawaban Peer To Peer Lending Terhadap Lender Apabila Terjadi Default Menurut Hukum Perlindungan Konsumen - Christopher Yehezkiel Bonardo Siahaan; Tuhana Tuhana (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Peer to peer lending creates a digital financing relationship between lender, borrower, and platform operator. The main legal issue arises when the borrower defaults and the lender suffers financial loss, while the operator often positions itself merely as an intermediary. This article analyzes the liability of peer to peer lending operators toward lenders in the perspective of Indonesian consumer protection law. This research uses normative legal research with statutory and conceptual approaches. The result shows that lenders may be positioned as financial services consumers because they use services provided by a financial services business actor. Default caused solely by the borrower's inability to repay is essentially a funding risk borne by the lender. However, the operator may be held liable when the lender's loss is caused by the operator's fault or negligence, including inaccurate risk disclosure, weak risk mitigation, improper credit scoring, misleading information, or unfair standard clauses that eliminate the operator's responsibility.